Analysis of Language Points on Kompas TV Youtube Channel "Legal Advisory Asks Ferdy Sambo about Elizer's Future Responsibilities to CCTV!" - Feny Rizka Antam; Yusni Khairul Amri (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
Reporting on the Kompas TV Youtube channel always provides interesting and up-to-date information so that it becomes a public discussion, one of which is the Ferdy Sambo case which has become a hot topic of conversation since July 2022. This writing aims to find out politeness in language and flouting of maxims on the Kompas TV Youtube channel entitled " Legal Counsel Ask Ferdy Sambo about Elizer's future responsibilities to the CCTV issue!”. The form of speech in this paper is a form of speech that adheres to the politeness principle and is translated into the maxims put forward by Leech in a pragmatic study. Collecting data using observing and note techniques then analyzed. As a result of writing, the Kompas TV Youtube channel adheres to the politeness principles (maxims), namely: the maxim of wisdom, the maxim of generosity, the maxim of appreciation, the maxim of modesty, the maxim of modesty, the maxim of agreement, the maxim of sympathy. Apart from that, there were also violations of the maxims, namely: a) the maxim of wisdom, b) the maxim of modesty, c) the maxim of sympathy.